Morphology of the larvae of Sandracottus femoralis Heller, 1934, and S. mixtus (Blanchard, 1843) and phylogenetic comparison with other known Aciliini (Coleoptera: Dytiscidae, Dytiscinae) - Alarie, Yves; Michat, Mariano C.; Shaverdo, Helena; Hájek, Jiří (Zootaxa, 2023)
We describe the larvae of the diving-beetle genus Sandracottus Sharp, 1882 based on S. femoralis Heller, 1934 and S. mixtus (Blanchard, 1843). We include detailed morphometric and chaetotaxic analyses of the cephalic capsule, head appendages, legs, terminal abdominal segment and urogomphi in order to discover useful characters for distinguishing Sandracottus larvae from those of other known Aciliini (Coleoptera: Dytiscidae, Dytiscinae). A provisional parsimony analysis based on larval characteristics of seven Aciliini species in four genera (Acilius Leach, 1817, Graphoderus Dejean, 1833, Sandracottus, Thermonectus Dejean, 1833) was conducted using the program TNT. A clade grouping Eretini and Aciliini stands out as the most strongly supported in this analysis. The tribe Aciliini finds itself monophyletic with also very good support. Our analysis, however, failed to depict any clear phylogenetic relationships within the Aciliini although each of the four genera studied emerged from our study as morphologically distinct.